VR _Virtual Reality Technology: il suo attuale paradosso - Tiziana Primavera (GEOmedia, 2023)
The contexts of economic development in the VR industry have revealed themselves unexpectedly slower than the analyzes let guess. There was no stop clearly, but the pace of growth proceeds rather slowly, despite forecasts enthusiastic connected to the Metaverse, which contemplates it. It is actually proceeding in close steps. It is therefore questionable whether consumer sentiment is actually inclined to the adoption of VR in daily life and if the market is consistent with these data.